2020
DOI: 10.3390/educsci10010016
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Graduate School Enrollment from Students in the Ronald E. McNair Post-Baccalaureate Program

Abstract: The Ronald E. McNair Post-Baccalaureate Achievement Program provides higher education institutions with federal funds to increase the doctoral attainment for students from disadvantaged backgrounds. We conducted a meta-analysis of the impact of the McNair program on graduate program enrollment. After an exhaustive literature search, we found 7 publications containing 13 studies that met the inclusion criteria. From these studies, we found that McNair program students were almost six times as likely to enroll i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…This study provides evidence that participants in the McNair Scholars program have high odds of enrolling in graduate school, yet this effect varies by institution. These results are consistent with other TRIO studies that found that campuses implement programs for marginalized students in different ways to adapt to their own contexts (Bowden & Belfield, 2015) as well as the most recent MSP research (e.g., Renbarger, 2019;Renbarger & Beaujean, 2020) that indicates MSPs benefit participants yet add nuance to the field regarding programmatic factors that relate to student success.…”
Section: Model 2 -Odds Of Enrolling In Graduate School Conditioned On Undergraduate Completionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study provides evidence that participants in the McNair Scholars program have high odds of enrolling in graduate school, yet this effect varies by institution. These results are consistent with other TRIO studies that found that campuses implement programs for marginalized students in different ways to adapt to their own contexts (Bowden & Belfield, 2015) as well as the most recent MSP research (e.g., Renbarger, 2019;Renbarger & Beaujean, 2020) that indicates MSPs benefit participants yet add nuance to the field regarding programmatic factors that relate to student success.…”
Section: Model 2 -Odds Of Enrolling In Graduate School Conditioned On Undergraduate Completionsupporting
confidence: 90%
“…The large majority of data on the utility of the MSP come from qualitative studies. In a review of the qualitative literature on the MSP, Renbarger (2020) Renbarger and Beaujean (2020) found that the MSP participants were six times more likely to enroll in graduate school compared to demographically similar peers. Given the researchers could only find a handful of quantitative studies and that few utilized large, representative samples, they stated that more quantitative work is warranted to understand the success (or lack of) for the overall program.…”
Section: Msps and Graduate Enrollmentmentioning
confidence: 99%
“…These larger reports have included annual program data from most, if not all, programs regarding participants' graduate school enrollment and degree attainment. Specifically focusing on the graduate school enrollment objective, programs had tripled the proportion of bachelor's degree recipients who entered graduate school over the course of three years (Seburn et al, 2005), and a recent meta-analysis has found that students in MSPs have six times the odds of enrolling in graduate school compared to students from similar backgrounds (Renbarger & Beaujean, 2020). Unfortunately, public program data includes only aggregated quantitative program information that is delayed and difficult to use, making it difficult for independent researchers to evaluate the program as a whole (Renbarger & Beaujean, 2020).…”
Section: Previous Research On Effectivenessmentioning
confidence: 99%
“…Specifically focusing on the graduate school enrollment objective, programs had tripled the proportion of bachelor's degree recipients who entered graduate school over the course of three years (Seburn et al, 2005), and a recent meta-analysis has found that students in MSPs have six times the odds of enrolling in graduate school compared to students from similar backgrounds (Renbarger & Beaujean, 2020). Unfortunately, public program data includes only aggregated quantitative program information that is delayed and difficult to use, making it difficult for independent researchers to evaluate the program as a whole (Renbarger & Beaujean, 2020). Additionally, no research has collectively examined all of the qualitative evidence that exists on this program in conjunction with these quantitative findings from federal and individual program reports to determine if MSPs are effective.…”
Section: Previous Research On Effectivenessmentioning
confidence: 99%
“…MSPs recruit rising junior or senior undergraduates, so scholars typically join the program for 1-2 years. To be admitted, students must come from a disadvantaged background, demonstrate high achievement (e.g., have good college grades), and exhibit the desire and motivation to obtain a doctoral degree (Renbarger & Beaujean, 2020). Disadvantaged background is defined as (a) coming from a low-income family (i.e., family income ≤ 150% of the federal poverty level), (b) being a first-generation college attendee, or (c) belonging to a racial/ethnic minority group (Seburn et al, 2005).…”
Section: Studentsmentioning
confidence: 99%